2014
DOI: 10.4066/amj.2014.2093
|View full text |Cite
|
Sign up to set email alerts
|

Proton pump inhibitors: Are we still prescribing them without valid indications?

Abstract: Inappropriate prescribing of PPIs without documented valid indications was prevalent among elderly patients at our tertiary teaching hospital in Singapore, providing evidence that shows a similar trend to PPI prescribing to data from Western countries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 23 publications
1
17
0
Order By: Relevance
“…Gastric acid suppressive agents were ceased in almost half of patients receiving them in the absence of a confirmed diagnosis of gastro‐oesophageal reflux or peptic ulcer disease, or because symptoms had long since resolved. Comparable rates of inappropriate overuse of proton pump inhibitors in hospitalised older patients have been described by others . This is of concern given the reported associations of increased risk of osteoporosis, Clostridium difficile colitis and community‐acquired pneumonia …”
Section: Discussionmentioning
confidence: 86%
“…Gastric acid suppressive agents were ceased in almost half of patients receiving them in the absence of a confirmed diagnosis of gastro‐oesophageal reflux or peptic ulcer disease, or because symptoms had long since resolved. Comparable rates of inappropriate overuse of proton pump inhibitors in hospitalised older patients have been described by others . This is of concern given the reported associations of increased risk of osteoporosis, Clostridium difficile colitis and community‐acquired pneumonia …”
Section: Discussionmentioning
confidence: 86%
“…Another independent factor that was associated with guidelines non‐compliance in this study and reported by previous studies was prescribing of low‐dose aspirin . Low‐dose aspirin is routinely used in primary and secondary prophylaxis of cardiovascular events.…”
Section: Discussionmentioning
confidence: 51%
“…As in other studies, the main factor for guidelines non‐compliance was coprescribing of PPIs with NSAIDs . Indeed, physicians prescribe PPIs for GIBP among patients using NSAIDs as ‘just in case’ without stratifying their patients based on their risk for GI complications.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations